Investigation of polyfunctional segments of non-obvious infrustructure of recreation and tourism sphere in national economy - Жупаненко, Анастасія Валеріївна (Technology audit and production reserves, 2015)
The article considers the theoretical approach to the identifying obvious and non-obvious components in the structure of recreation and tourism sphere on the basis of the mono- and polyfunctionality of their segments. This approach on contrast to others gives an opportunity to consider all spheres of business, where enterprises are polyfunctional. Their basic functions become a background of recreation and tourism. Polyfunctionality is considered as the ability of an enterprise to perform several functions simultaneously, where the recreation and tourism are based on the others such as nature saving, healing, cultural, educational etc. The definitions of the non-obvious infrastructure, its segments, subjects and objects are defined on the basis of three approaches (theoretical-economical, structural and functional). Theoretically interpreted economic essence of non-obvious infrastructure for the national economy and instruments of governmental influence at its functioning and development through implementation of governmental tourism policy, which will be able to activate all spheres of national economy, referred as non-obvious infrastructure.